A prospective nonrandomized phase I/II study of carbon ion radiotherapy in a favorable subset of locally advanced non–small cell lung cancer (NSCLC). Issue 8 (13th January 2015) - Takahashi, Wataru; Nakajima, Mio; Yamamoto, Naoyoshi; Yamashita, Hideomi; Nakagawa, Keiichi; Miyamoto, Tadaaki; Tsuji, Hiroshi; Kamada, Tadashi; Fujisawa, Takehiko
<x xml:space="preserve">Abstract</x> BACKGROUND Although concurrent chemoradiotherapy (CCRT) has become the standard approach for unresectable locally advanced non–small cell lung cancer (LA‐NSCLC), most patients are not candidates for this treatment because of comorbidities. We evaluated the safety and efficacy of carbon ion radiotherapy (CIRT) in LA‐NSCLC patients. METHODS Patients with stage IIA to IIIA (UICC 7th edition) LA‐NSCLC were enrolled in a sequential phase I/II trial. For a phase I dose escalation study, the total prescribed dose was increased by 4 Gray equivalents (GyE) in 2 steps, from 68 to 72 GyE and then to 76 GyE, using 16 fractions over 4 weeks. After determining the recommended dose, the phase II trial was started in an expanded cohort. RESULTS Of the 36 patients treated in phase I, 2 grade 3 adverse events (radiation pneumonitis and tracheoesophageal fistula) were observed in the 76 GyE group. Accordingly, for phase II, the next consecutive 26 patients were treated with 72 GyE, with no grade 3 to 5 toxicities resulting. A total of 62 eligible patients were recruited. The majority of patients (49 of 62) were N0 or N1 patients, and the rest (13 of 62) were single‐station N2 patients. The median follow‐up period was 25.2 months. The 2‐year local control rate (LCR) and overall survival (OS) for the entire cohort were 93.1% and 51.9%, respectively. In particular, patients with cT3‐4N0 had an excellent prognosis; the 2‐year OS and LCR were 69.3% and 100%, respectively. CONCLUSIONS Short‐course CIRT monotherapy shows promise as an effective nonsurgical treatment for inoperable LA‐NSCLC. Cancer 2015;121:1321–1327. © 2014 American Cancer Society.